Biosynthesis of nickel oxide (NiO) nanoparticles from cactus plant extract. (2021) - Gebretinsae, H.G.; Tsegay, M.G.; Nuru, Z.Y.
Abstract: P-type NiO powders with an average crystallite size of 16 nm as shown by x-ray diffraction analysis were produced via biosynthesis using cactus plant extract. SEM showed that the NiO powders consisted of particles with sizes in the 20–35 nm range. XPS confirmed the chemical composition and chemical state of the NiO. From Raman spectroscopy, strong 1 phonon vibrations at ∼548.4 cm −1 and the existence strongest band at ∼1730 cm −1 to a two-magnon (2 M) scattering of bulk NiO associated with Ni 2+ -O 2− -Ni 2+ super-exchange symmetry confirmed that biosynthesized NiO powders were defect-rich in surface effects. Through these findings the use of natural Cactus extracts is hereby shown to be a cost-effective and environmentally friendly alternative for preparing Nickel oxide nanosized powders that can be of use in a variety of energy storage applications.